2019
DOI: 10.1186/s13018-019-1277-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SDF-1 with biphasic ceramic-like bone graft on the repair of rabbit radial defect

Abstract: Background This study aimed to investigate the effects of stromal cell-derived factor-1 (SDF-1) on biphasic ceramic-like biologic bone (BCBB) in vivo on the repair of large segment bone defect in rabbits. Methods A large-segment radius defect model of the rabbits was constructed. In the experimental group, BCBB with SDF-1 sustained-release system were implanted into the bone defect site. Other three groups including normal control, autologous bone graft, and BCBB implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…Among all the groups, the PCL@BG20-GelMA/SDF-1α group showed the largest amount and greatest thickness of new bone, which was consistent with the results of micro-CT analysis. These results indicate that the addition of SDF-1α can promote the aggregation of rBMSCs, ensure that bone defect sites have a sufficient cell supply, and promote the rapid formation of new bone tissue, which was also consistent with the findings of Wang et al [ 37 ]. Wang et al [ 37 ] found that scaffolds carrying SDF-1α exhibited better bone conduction and induction ability.…”
Section: Resultssupporting
confidence: 91%
“…Among all the groups, the PCL@BG20-GelMA/SDF-1α group showed the largest amount and greatest thickness of new bone, which was consistent with the results of micro-CT analysis. These results indicate that the addition of SDF-1α can promote the aggregation of rBMSCs, ensure that bone defect sites have a sufficient cell supply, and promote the rapid formation of new bone tissue, which was also consistent with the findings of Wang et al [ 37 ]. Wang et al [ 37 ] found that scaffolds carrying SDF-1α exhibited better bone conduction and induction ability.…”
Section: Resultssupporting
confidence: 91%
“…Defect non-union represents the most dramatic clinical scenario, once the surgeon has to deal with a critical sized bone gap, and just few options are available for modify the devastated biological and mechanical environments (GIANNOUDIS;MARSH, 2007). Numerous biomaterials have been investigated in the field of bone tissue engineering and the critical sized bone defect has been the most common and effective experimental model for testing then (CASTAÑEDA et al, 2006;NIELSEN;KARRING;GOGOLEWSKI, 1992;NIEMEYER et al, 2010;WANG et al, 2019;ZHANG et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that using a radial ostectomy without cutting the ulna allows early and full limb function in rabbits, which is remarkably desirable (GEIGER et al, 2007;NIEMEYER et al, 2010;ZHAO et al, 2016). The bone region may vary between diaphyseal or metaphyseal, being the first one most commonly used to perform critical size defects in rabbits (CSD) (MA et al, 2018;WANG et al, 2019;XIE et al, 2017;ZHANG et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, an ascending series of alcohol rinses were used for sample dehydration, and specimens were embedded in paraplast (Sherwood Medical Industries, Deland, FL, USA). Embedded samples were sectioned to a 5 μm thickness with a microtome (Cambridge Instruments, Germany), and slides were stained with hematoxylin and eosin (H&E), Masson-Goldner trichrome (GT), and Van Gieson’s (VG) for microscopic observation ( 27 , 28 ). In the VG microscopic images, the new bone area was measured for quantitative analysis with the Image J program (National Institute of Health, Stapleton, NY, United States).…”
Section: Methodsmentioning
confidence: 99%